Discovery of a second type of high-T_{S} magnetic spiral in layered YBaCuFeO_{5} type perovskites - Ruyong Li; Arnau Romaguera; Oscar Fabelo; Xiaodong Zhang; Francois Fauth; José Luis García-Muñoz (Physical Review Research)
Layered Cu/Fe perovskites with a YBaCuFeO_{5} structure have attracted significant attention owing to the high thermal stability (T_{S}) of their incommensurate spiral magnetic phase. The intrinsic coupling between spin and ferroelectric orders in these cycloidally ordered multiferroics makes them among the most promising spin-driven magnetoelectric multiferroic candidates. In this system, strong in-plane antiferromagnetic couplings lead to collinearly ordered magnetic planes with spin directions alternating with periodicity (k_{x}, k_{y}) = (0.5, 0.5), while spin propagation along the perpendicular direction is governed by competing frustrated magnetic couplings of varying signs and strengths. In compounds of this family studied to date, the incommensurate spiral order emerges below T_{S} due to correlated canting of ferromagnetically coupled spins in bipyramidal layers (k_{z}=0.5→0.5±q_{S}). Here, we demonstrate that a spiral magnetic ground state can also arise from a distinct precursor collinear spin configuration, where, above T_{S}, spins in the bipyramids are initially antiferromagnetically coupled (k_{z}=0→±q_{S}). This newly observed spiral magnetic transition, identified and investigated in YBaCu_{1−x}M_{x}FeO_{5} compounds (M: Co, Zn), exists beyond the triple magnetic point, previously considered the critical limit for the ordering of the magnetic spiral in YBaCuFeO_{5}. In the compounds investigated, the new spiral state persists in this region, stabilizing at temperatures up to 365 K.